Charge Transfer and Photocatalytic Activity in CuO/TiO2 Nanoparticle Heterojunctions Synthesised through a Rapid, One‐Pot, Microwave Solvothermal Route. Issue 11 (1st June 2015) - Moniz, Savio J. A.; Tang, Junwang
Abstract The front cover artwork for Issue 11/2015 is provided by the group of Dr. Junwang Tang, University College London. The image shows how solar energy can be utilised to efficiently decontaminate wastewater supplies by using nanostructured heterojunction photocatalysts. See the Full Paper itself at http://dx.doi.org/10.1002/cctc.201500315.